2021
DOI: 10.3390/brainsci11020246
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Clinical Workflow May Lead to Increased Diagnostic Precision in Hereditary Spastic Paraplegias and Cerebellar Ataxias: A Single Center Experience

Abstract: The molecular characterization of Hereditary Spastic Paraplegias (HSP) and inherited cerebellar ataxias (CA) is challenged by their clinical and molecular heterogeneity. The recent application of Next Generation Sequencing (NGS) technologies is increasing the diagnostic rate, which can be influenced by patients’ selection. To assess if a clinical diagnosis of CA/HSP received in a third-level reference center might impact the molecular diagnostic yield, we retrospectively evaluated the molecular diagnostic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition, half of the cases with molecular diagnosis could be confirmed before implementation of WES. It has been demonstrated that by integrating mode of inheritance and pertinent clinical data, disease-related genetic testing followed by multigene panels may improve diagnostic yield for HSP and HCA (22). Furthermore, this and our study suggest that the integrated testing flowchart not only helps to guide a time and cost-efficient molecular testing in the new generation sequencing era, but also facilitates genotype-phenotype correlation in diagnosing the heterogeneous neurogenetic disorders.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, half of the cases with molecular diagnosis could be confirmed before implementation of WES. It has been demonstrated that by integrating mode of inheritance and pertinent clinical data, disease-related genetic testing followed by multigene panels may improve diagnostic yield for HSP and HCA (22). Furthermore, this and our study suggest that the integrated testing flowchart not only helps to guide a time and cost-efficient molecular testing in the new generation sequencing era, but also facilitates genotype-phenotype correlation in diagnosing the heterogeneous neurogenetic disorders.…”
Section: Discussionmentioning
confidence: 60%
“…However, the outcomes achieved combining in silico and 3D-modeling studies allowed us to speculate on the potential causative role of the other variants (i.e., those whose 3D protein structure was not available) Interestingly, the SCAR genes considered to be frequent in the pre-NGS era (e.g., ATM, SETX, and APTX) were less common than expected in our cohort, or even absent (i.e., SACS). This could be related to the prevalently retrospective nature of our study, in which patients with peculiar phenotypes, such as those resembling ataxia-telangectasia, ataxia with oculomotor apraxia, and autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS), underwent direct Sanger sequencing prior to inclusion [105].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study published in 2021 estimated the diagnostic yield in 124 SCA patients from 102 families in Italy, with a reported total diagnosis rate of 52%. AD-SCA patients had the highest diagnostic yield (64.5%) among the SCA cases, of which the most frequent subtype was SCA2, followed by SCA1, SCA3, SCA6, and SCA7 [53]. Furthermore, the genetic epidemiology of SCA, like that of any rare disease, is affected by founder effect.…”
Section: Spinocerebellar Ataxiasmentioning
confidence: 99%